Implementação da notificação de cobrança por mala direta sob enfoque do Lean Thinking: um estudo de caso antes e depois em uma cooperativa de planos odontológicos - Lima, Jerry Araújo de (Brasil, 2024)
In the context of global transformation, with an increasingly competitive and innovative market, offering affordable, fast, and higher-quality services becomes necessary, leading organizations to seek ways to eliminate waste and streamline processes. Thus, this article aims to investigate the impact of adopting the Lean Thinking in a dental plan cooperative. To achieve this, a case study was conducted, involving literature research, observation, interviews, and a comparative analysis of process cycles. The focus of the analysis was the implementation of direct mail notification for invoices, which replaced a manual process. The results showed that the change resulted in a significant time reduction of approximately 88.36%, in addition to improving communication with customers. The conclusions indicate that the Lean philosophy has the potential to optimize administrative operations, improve customer relationships, and suggest possibilities for improvements in other organizational processes.